Implementing the Global University Publications Licence: a new open scholarship model for advocating change - Zhou, Jiafeng; Ke, Wu; Smyth, Neil (UKSG in association with Ubiquity Press, 2021)
Universities want a voluntary, non-exclusive licence from authors to disseminate publications. This practitioner case study explores an innovative model to communicate and advance open and equitable scholarship through the implementation of the Global University Publications Licence at the University of Nottingham Ningbo China. This article explains the licensing policy and key influences, including, the copyright law of the People’s Republic of China and the Declaration on Research Assessment (DORA). The University approved the Global University Publications Licence, with implementation from 1 August 2019. It is available in Chinese and English. Since implementation, the University has retained rights for 74% of research publications submitted. 100% of those publications are available through the University with a CC-BY licence and zero embargo. The open scholarship model provides an equitable approach to versions and citation. The article concludes by suggesting university libraries can exploit copyright law in China to progress open scholarship strategies, including recognition of employers as authors of works, a priority right to the exploitation of works and an embargo protection of two years after the completion of the work. The author’s final version of publications can be open, discoverable, cited and preserved through trusted universities with global reputations for high-quality research.